MicroRNA-210 expression during childbirth and postpartum as a potential biomarker of acute fetal hypoxia - Vonkova, Barbara; Blahakova, Ivona; Hruban, Lukas; Janku, Petr; Pospisilova, Sarka (Biomedical papers, 2019)
Objective: To explore whether miR-210 expression can be used as a diagnostic and prognostic marker in acute fetal hypoxia. Methods: Whole blood samples of 29 women and their fetuses without hypoxia and 24 women and their fetuses with hypoxia were analysed in this study. Reverse transcription and quantitative real-time PCR were used to measure the expression of miR-210. Expression level differences between the control and hypoxic group in labour time and postpartum change fold were analyzed by standard statistical tests. Results: We confirmed that miR-210 is significantly more upregulated in fetal blood with acute hypoxia when compared to maternal blood (P Conclusions: Our study confirmed miR-210 upregulation in the blood of pregnant women with acute fetal hypoxia at the time of labour compared to pregnant women without acute fetal hypoxia. Additional investigation should be done to determine miR-210 clearance and the possibility of using miR-210 as a diagnostic and prognostic marker.
Keywords: microRNA-210; acute fetal hypoxia; postpartum; clearance of miR-210